Postharvest maturation of Pouteria lucuma: Effect of storage conditions on physicochemical components, metabolites and antioxidant and hypoglycemic capacity - Inga, Marianela (2021)
Inadequate storage conditions can affect the sensory, physicochemical, and functional properties of tropical fruits such as Pouteria lucuma; which is a climacteric fruit, with a pleasant aroma and flavor; Peru being the main producer and exporter of this fruit, postharvest storage conditions have not been studied to maintain its properties. The objective of the research was to evaluate the effect of the storage conditions on the main physicochemical components, primary and secondary metabolites, antioxidant, and hypoglycemic capacity during postharvest ripening, under two storage conditions: ambient (29 °C and 70% RH) and climatic chamber (15 °C and 90% RH). Regarding the physicochemical characteristics, the state of maturity influenced acidity, pH, reducing sugars, starch, dietary fiber, firmness, pulp color and epicarp. In climate-controlled storage, glucose is the only metabolite that increases; while fructose, alcohol sugars and amino acids (Ala and Val), present higher values ​​under ambient conditions; sucrose, organic acids, amino acids (Tyr, Glu, Asp and Thr), β-carotene, total phenolic compounds and total carotenoids were not affected by the type of storage. The measure of antioxidant and hypoglycemic capacity decreased significantly (p < 0,05), showing to be affected only by the state of maturity. The study of the carotenoid profile according to its spectrum (UV-vis) showed the presence of the group of xanthophylls. The results indicate that the state of maturity concerning the storage condition influenced most of the changes studied.